Oil and Gas Potential of Sihapas Formation, Central Sumatra Basin Based on Water Saturation (Sw) and TOC - Dewanto, O; Mulyatno, B S; Wibowo, R C; Kumalasari , I N; Tamara, D A; Yuliantina, A (Fakultas Teknik Universitas Lampung, 2024)
The potential of oil and gas in the Sihapas Formation has not been extensively studied, especially in terms of reservoirs based on water saturation (Sw). Few researchers have examined the source rock potential in the Sihapas Formation. To address this, researchers conducted a study on two wells to determine the potential of oil and gas in the Sihapas Formation using Sw values and source rock identification. The target areas and oil and gas content were identified using the logging method based on Sw values. For source rock identification, the logging method determined the TOC value, which was then compared with TOC core data from other researchers. Additionally, kerogen type and maturation in other wells in the Central Sumatra Basin were considered. The results showed several target areas in the Sihapas Formation with Sw values ranging from 10% to 62%, indicating the presence of oil and gas. The source rock areas in the Sihapas and Pematang Formations were found to be in good condition based on TOC calculation results, with TOC values of 1.94%-3.53% in the Sihapas Formation and 5.58%-18.54% in the Pematang Formation. These TOC results were consistent with TOC cores from other researchers in the Central Sumatra Basin. The kerogen type was identified as I/II and immature. The study concluded that the Sihapas Formation has potential oil and gas reservoirs, with good source rock conditions indicated by Sw values, TOC, kerogen type, and maturation data.